Permainan Tradisional Tapa Gala Berbasis Kearifan Lokal sebagai Penguatan Karakter Gotong Royong dalam Implementasi Profil Pelajar Pancasila - Satriawan, Rabwan; Amar, Khairul; Fitriani, Ainun (Indonesian Journal of Physical Education and Sport Science, 2023)
Study Purpose. This study aims to describe the traditional tapa gala game based on local wisdom as a strengthening of mutual cooperation character in the implementation of the Pancasila Student Profile for elementary school students in Physical Education Sports and Health learning. Materials and methods. This research is a literature study research, by searching relevant literature to gain an in-depth understanding of the concepts of traditional tapa gala games based on local wisdom as a strengthening of mutual cooperation character in the implementation of the Pancasila student profile in Physical Education Sports and Health learning. Results. Mutual cooperation character education in traditional tapa gala game sports shows that traditional tapa gala game sports contains various aspects of mutual cooperation character education. The traditional game sport tapa gala has the potential to be implemented in Physical Education Sports and Health learning in an effort to strengthen the character of mutual cooperation to promote cooperation between students in learning. Conclusion. The traditional game sport tapa gala based on local wisdom is also a local cultural heritage that must be preserved by students in learning Physical Education Sports and Health as a strengthening of mutual cooperation character to implement the Pancasila Student Profile.